DIAGNOSIS OF BREAST CANCER IN BRAZIL: REFLECTION ON THE IMPACT OF THE COVID-19 - Ramos, Maria Fernanda Passos Rocha; Ramos, Dandara Rocha; Ramos, Paulus Fabricio Mascarenhas; Avena, Katia de Miranda (Mastology, 2026)
Objective: The objective of this study was to verify if the COVID-19 pandemic impacted the screening of breast cancer in women in Brazil. Methods: This is an observational, cross-sectional study with a descriptive and quantitative approach, carried out with secondary data provided by the Cancer Information System (SISCAN/DATASUS), considering two temporal clippings — before the pandemic (2015–2019) and during the pandemic (2020 and 2021). Women diagnosed with breast cancer who underwent mammography between 2015 and 2021 were included in the study. Review by the Research Ethics Committee was waived because public, aggregated, and unidentified data were used. Results: Between 2015 and 2021, 17,229,218 mammograms were performed in Brazil. The temporal analysis showed a gradual upward trend in all years, reaching 49.6% growth in the period before the pandemic (from 2,047,504 mammograms in 2015 to 3,063,618 mammograms in 2019). During the COVID-19 pandemic, there was a change in the Brazilian epidemiological behavior, as evidenced by a significant decrease in the number of examinations performed. In 2020, 1,864,891 mammograms were recorded, representing a 39.1% drop, while in 2021, 2,606,074 mammograms were recorded, representing a 39.7% increase over the previous year, but if compared to the last pre-pandemic year, there is an important decrease in the number of mammograms performed (14.9%). Besides this, another consequence was the underdiagnosis of some diseases, such as breast cancer. The estimate stipulated by the National Cancer Institute (INCA) for each year of the triennium between 2020 and 2022 was 66,280 new cases of breast cancer in Brazil. As with mammograms, in 2020, there was a 10.3% drop in diagnoses (n=46,509), which represent only 70.2% of the estimate made by INCA for 2020. In 2021, this drop was even more significant (n=24,446), representing only 36.9% of the expected for the period. Conclusion: Due to the emergence of COVID-19 and the magnitude of the pandemic, there was an epidemiological change in public health in Brazil, significantly impacting the screening, monitoring, and treatment of diseases with high incidence in the country. It is believed that this panorama will reflect in the increase of cases and their severity, besides impacting the costs of public health worldwide.